(untitled) (International Journal of Engineering and Computer Science, 2017)
The Design and Implementation of Robot Arm Control System is the subject of this thesis. To achieve the prototype, an appropriate payload was chosen and its torque requirements were carefully calculated. This formed the basis of selecting a motor of appropriate torque. A permanent magnet Stepper Motor was chosen for use in constructing the prototype because it delivers a known incremental step for each pattern sent to the motor. The prototype used four stepper motors, one at the ankle, one at the base, one at the wrist and one at the shoulder. This made possible, four axis of movement for the Robot Arm. Although a stepper motor can be used to carry out different process control tasks, the particular task assigned to the prototype is a pick and drop process control. The actions required for the Robot Arm during a pick and drop process was subdivided into twelve sub tasks. Each sub task led to a flowchart which guided the development of the corresponding microcontroller software that helps to achieve the sub tasks. A main program was designed and developed which calls each of the twelve sub-routines for pick and drop activities in sequence, at appropriate times in order to achieve the pick and drop process. The 8051 Microcontroller was selected because of its ready availability as well as its features that match the pick and drop operation. A fully expanded state transition table and a content addressable memory were used to achieve smooth transitions of the Robot control stepper motors. User friendliness was achieved by providing a Liquid Crystal Display and a Keypad. The system can also be reprogrammed to perform other tasks such as painting, welding, pounding, among others, provided the end effectors are modified to match the operation envisaged. The prototype testing and evaluation show that it met the criteria listed in the design objectives.